The optimization of P-i-N power switching diode in term of reverse breakdown voltage and electrostatic disharge performance - See, Jian Hao author (Institute of Nano Electronic Engineering, 2017)
The research scope in this research is mainly divided into four main stages. The initial stage of this research includes identifying the existing problem of both low range ( < 300 V ) and high range ( > 300 V ) voltage power switching diode. Second stage of the research scope is about validating for the improvement hypothesis of power switching diode via TCAD simulation. For third stage of research scope, the implementation of the improvement that validated from the TCAD simulation result on the wafer fabrication using DOE approach. During the third stage, validation with fabrication of power switching diode is executed to get the real result. The DOE method is applied in the third part together with power switching diode fabrication to prepare samples for analysis and verification. Fabrication of a power switching diode included oxidation, photolithography, etching and metallization process.